Monodentate Phosphinoamine Nickel Complex Supported on a Metal–Organic Framework for High‐Performance Ethylene Dimerization - Wenmiao Chen (5657528) (2024)
Ethylene dimerization is an efficient industrial chemical process to produce 1‐butene, with demanding selectivity and activity requirements on new catalytic systems. Herein, a series of monodentate phosphinoamine‐nickel complexes immobilized on UiO‐66 are described for ethylene dimerization. These catalysts display extensive molecular tunability of the ligand similar to organometallic catalysis, while maintaining the high stability attributed to the metal–organic framework (MOF) scaffold. The highly flexible postsynthetic modification method enables this study to prepare MOFs functionalized with five different substituted phosphines and 3 N‐containing ligands and identify the optimal catalyst UiO‐66‐L5‐NiCl2 with isopropyl substituted nickel mono‐phosphinoamine complex. This catalyst shows a remarkable activity and selectivity with a TOF of 29 000 (molethyl/molNi/h) and 99% selectivity for 1‐butene under ethylene pressure of 15 bar. The catalyst is also applicable for continuous production in the packed column micro‐reactor with a TON of 72 000 (molethyl/molNi). The mechanistic insight for the ethylene oligomerization has been examined by density functional theory (DFT) calculations. The calculated energy profiles for homogeneous complexes and truncated MOF models reveal varying rate‐determining step as β‐hydrogen elimination and migratory insertion, respectively. The activation barrier of UiO‐66‐L5‐NiCl2 is lower than other systems, possibly due to the restriction effect caused by clusters and ligands. A comprehensive analysis of the structural parameters of catalysts shows that the cone angle as steric descriptor and butene desorption energy as thermodynamic descriptor can be applied to estimate the reactivity turnover frequency (TOF) with the optimum for UiO‐66‐L5‐NiCl2. This work represents the systematic optimization of ligand effect through combination of experimental and theoretical data and presents a proof‐of‐concept for ethylene dimerization catalyst through simple heterogenization of organometallic catalyst on MOF. Other Information Published in: Advanced Science License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1002/advs.202309540